Desenvolvimento de formulação contendo extratos de Bromelia laciniosa com atividade antibacteriana frente a cepas de Staphylococcus aureus - Pontes, Michelle Cruz (2021)
This study will be divided into chapters. The first chapter aims to investigate the chemical constituents and biological activities of aerial parts of Bromelia laciniosa. For this, the chemical composition of the chloroform (Bl-CHCl3), ethyl acetate (Bl-AcOEt) and ethanolic (Bl-EtOH) extracts from the leaves of B. laciniosa were evaluated by HPLC-DAD-ESI-MS/MS and by NMR. The contents of total phenols, toxicity and antioxidant activities, in vitro, of the extracts were also evaluated. In the analysis by HPLC-DAD-IES-EM/EM, 18 constituents were identified, especially phenylpropanoids, mono and diglycerides, while by NMR, it resulted in the identification of 1,3-O-dicafeoylglycerol, the major compound of the Bl-AcOEt extract, which is highlighted for its antioxidant and antibacterial potential against S. aureus MRSA. The second chapter involved the steps of preparation and evaluation of the biological potential of formulations, with the objective of developing herbal formulations containing B. laciniosa extracts with antibacterial action against strains of S. aureus MRSA. Thus, the bioactive phenolic profile of the species was described by HPLC-DAD, and the antibacterial formulations of Lanette WB® were developed from extracts of B. laciniosa leaves, also evaluating the antioxidant and antibacterial activities of the preparations. Formulation F6 (10% of Bl-AcOEt) exhibited pronounced antioxidant effect and showed anti-staphylococcal activity against three clinical isolates of S. aureus MRSA and standard strain, exhibiting a superior effect to the reference antimicrobial. The results confirm the promising potential of B. laciniosa as a source of drugs for the treatment of bacterial infections. This is the first report on or development of pharmaceutical preparations containing extract of B. laciniosa.